2010
DOI: 10.1097/yct.0b013e3181a95dbe
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of QT Interval and QT Dispersion During Electroconvulsive Therapy Using Computerized Measurements

Abstract: The QTc interval, QTD, and QTcD, which were associated with increased risks of ventricular arrhythmias, increased significantly before anesthetic induction in patients with major depression. Electrical stimulus during ECT induced further increases of the QTD and QTcD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…With respect to the QTc interval, it has been pointed out that mECT can provoke prolongation of QTc intervals [17,18]. In our patient, the QTc interval spread to 0.46 s following the convulsions.…”
Section: Discussionmentioning
confidence: 89%
“…With respect to the QTc interval, it has been pointed out that mECT can provoke prolongation of QTc intervals [17,18]. In our patient, the QTc interval spread to 0.46 s following the convulsions.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, it is necessary to consider the effects of autonomic nervous system activity or catecholamine secretion from the adrenal medulla in response to remifentanil and mECT. Fourth, various antidepressants and antipsychotics may prolong the QT and increase the QTd prior to mECT, as shown in our previous report [15]. In fact, the prolongation in QT and QTd in patients taking these drugs prior mECT was enhanced by electrical stimulation under anesthesia in our previous report.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, QT and QTD appear to correlate with autonomic regulation instability [4][5][6] and are potential causes of ventricular arrhythmias [7] or severe cardiac adverse events [8], such as myocardial infarction or cardiac sudden death [9][10][11][12][13]. In addition, several reports have indicated that both values increase as a result of various perioperative surgical procedures [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A QTc greater than 500 ms has been reported to be highly abnormal for both men and women by guidelines provided by the Food and Drug Administration in 2012 . Moreover, QTc has been reported to possibly change dramatically and rapidly (i.e., within minutes) during ECT . Thus, QTc should be monitored with high time resolution to detect the high‐risk period (i.e., periods when QTc increases by more than 500 ms) to prevent fatal arrhythmia during ECT.…”
Section: Discussionmentioning
confidence: 99%